Creating an animation-enhanced video library of hepato-pancreato-biliary and transplantation surgical procedures. (2nd April 2016) - Fung, Albert; Kelly, Paul; Tait, Gordon; Greig, Paul D.; McGilvray, Ian D.
Abstract : The potential for integrating real-time surgical video and state-of-the art animation techniques has not been widely applied to surgical education. This paper describes the use of new technology for creating videos of liver, pancreas and transplant surgery, annotating them with 3D animations, resulting in a freely-accessible online resource: The Toronto Video Atlas of Liver, Pancreas and Transplant Surgery (http://tvasurg.ca ). The atlas complements the teaching provided to trainees in the operating room, and the techniques described in this study can be readily adapted by other surgical training programmes.